En Hommage: The Contributions of I. William Zartman. (25th September 2017) - Crump, Larry; Terrence Hopmann, P.; Lyons, Terrence; Spector, Bertram
Abstract: In this tribute to the 2001 International Association for Conflict Management Lifetime Achievement Award recipient, we recognize and celebrate the work of I. William (Bill) Zartman—a prolific scholar who has offered understanding and insight about conflict, negotiation, and peace throughout a remarkable career. We specifically highlight Zartman's substantial contribution to scholarship, knowledge, and understanding in four areas: international negotiation; negotiation and conflict in Africa; negotiation complexity and its analysis; and his work as a teacher and educator. The article closes by providing Bill Zartman with an opportunity to reflect and impart words of wisdom to negotiation and conflict management students and scholars.